GREEN FITNESS: THE IMPACT OF NATURE ON SPORT AND PHYSICAL ACTIVITY IMPROVEMENTS - Shukhrat Yusupovich Rahmanov (American Journals Publishing, 2024)
The article is dedicated to the topic of "Green Fitness" and its importance for health and well-being. Green fitness involves engaging in sports activities outdoors in a natural environment, such as running, yoga, cross-country running, cycling, and open water swimming. The article discusses the benefits of each type of activity for physical and mental health, as well as their impact on overall human well-being. Practical advice is also provided on organizing green fitness activities and ensuring safety during outdoor workouts. This article aims to draw attention to the importance of outdoor sports and inspire readers to lead an active lifestyle in harmony with nature.